Optimization of One-Pot Microwave-Assisted Ferrofluid Nanoparticles Synthesis Using Response Surface Methodology - Kamel Ariffin, Maryam Farhana (Institute of Electrical and Electronics Engineers Inc., 2018)
Microwave-assisted (MWA) technique has been used in the syntheses area as it has many advantages over the conventional routes. Optimization of one-pot synthesis of ferrofluid was conducted using domestic 2.45 GHz microwave (MW). The nanoparticles were synthesized in an aqueous solution of FeCl3.6H2O as precursor and NH3 as nucleating agent. Although there are a number of reports on the MWA iron oxide nanoparticle synthesis, a quantitative optimization study on the process is still lacking. Here, MW parameters were manipulated in order to optimize the synthesis. The optimization was designed and statistically analyzed using face-centered central composite design software. The optimized conditions for MWA synthesis of ferrofluid were 80 °C reaction temperature, 14 min reaction time at 300 W producing 0.338 g of magnetic nanoparticles. Based on the characteristic studies done on synthesized ferrofluid by using X-ray diffraction, field emission scanning electron microscope, antitransmit receive (ATR) Fourier-transform infrared spectroscopy, and vibrating sample magnetometer, the nanoparticles possessed the same structure as the standard maghemite with good magnetic properties. The process produces ferrofluid of high purity with an average crystallite size of 15 nm.